Analisis Pengaruh Pertumbuhan Ekonomi, Aglomerasi Industri, PMDN, Belanja Pemerintah, dan IPM Terhadap Ketimpangan Wilayah di Kawasan KEDUNGSEPUR Tahun 2011-2020 - Ade Tiara Sukmawati; Mulyo Hendarto Robertus (Diponegoro Journal of Economics, 2023)
Inequality is a common problem that occurs along with the economic development process of a region. The difference in endowment factors in each region is the cause of the widening level of inequality. This study aims to analyse the effect of economic growth, industrial agglomeration, domestic investment (PMDN), government spending, and Human Development Index (HDI) on regional inequality in the KEDUNGSEPUR Region in 2011-2020. The level of regional inequality is calculated using Theil's Entropy Index. This study uses the Generalised Least Square (GLS) regression analysis method with a fixed effect model. The data used is panel data which includes cross section of 6 regencies/cities in the KEDUNGSEPUR region and time series from 2011-2020. The results show that the variables of economic growth, industrial agglomeration, and government spending partially have a negative and significant effect on regional inequality in the KEDUNGSEPUR Region. The Human Development Index (HDI) partially has a positive and significant effect on regional inequality, while domestic investment (PMDN) partially has an insignificant effect on regional inequality.